Corn Supply Chain in Central Java Province: Marketing Channel Efficiency and Chain Institutional Performance Approach - Zuhri, Nur Muttaqien; Rahayu, Endang Siti; Kusnandar, Kusnandar; Harisudin, Mohamad (AIBPM Publisher, 2023)
Increasing corn production requires a supply chain to channel production from farmers to consumers. The supply chain of corn as a raw material for animal feed in Central Java Province is not yet well managed, because each farmer or business is still carried out individually. The aim of the study was to analyze the supply chain picture based on the Food Supply Chain Network and the efficiency of the corn agribusiness supply chain in Central Java. Sampling techniques from farmers using proportional random sampling and snowball sampling methods will lead researchers to the next informant or to related institutions to the final consumer. Data analysis uses the FSCN, Marketing Margin, Farmer's Share and DEA methods. There are 5 corn agribusiness marketing channels in Central Java Province. Marketing margin and farmer's share with Farmer-Cooperative-Consumer chain being the most efficient. Farmer-Village Trader-SubDistrict Trader-District Trader-Consumer marketing channel being the least efficient. Technical efficiency at the farmer level was 2%, at the village trader level 40%, at the subdistrict and district trader levels 37.5%, at the cooperative level 66.67%, at the animal feed company level 40% and at the poultry farmer level 25%.